Pengembangan Model Pembelajaran Matematika Berbasis Reward dan Punishment untuk Meningkatkan Motivasi Belajar pada Siswa Kelas VI MI Khozinatul Ulum Blora - Sajudin, Muhammad; Zainal Abidin, Muhammad; Habibah, Nur (Jurnal Studi Islam dan Sosial, 2022)
Motivation to learn is very important for students, is no exception in mathematics. Students who have high learning motivation will have implications for good and satisfying learning outcomes. One of the learning models that is considered the most effective way to encourage students to be more enthusiastic about learning is reward and punishment. The formulation of the problems in this study are: 1) How is the development of a mathematics-based mathematics learning model and punishment to increase motivation to learn in class VI MI Khozinatul Ulum Blora students? 2) How is a hypothetical mathematical learning model based on English and punishment. 3) How is the tested model of mathematics-based mathematics learning and punishment. The purpose of this study are: 1) To analyze mathematical learning models based on rewards and punishments in increasing learning motivation. 2) To get a hypothetical design, the development of reward and punishment based mathematics learning models to increase learning motivation. 3) To analyze and obtain reward and punishment based mathematical learning models that are tested to increase learning motivation. 4) Mathematics-based reward and punishment based learning models to improve learning motivation. The method of research and development by developing a learning product that represents the findings and observations that have been made. R and D are done in key stages until it gets a test result across a key foundation for product production. The result of this study after fulfilling the steps is obtained a test model for follow-up with a hypothetical model's evaluation, including past analysis of the clumping process for the students' learning motivation. Later the test model became the basis for making the product of the study manual of reward and punishment for teachers.